Genetic variations in the SOCS3 gene in patients with Graves' ophthalmopathy. Issue 6 (13th March 2015) - Yan, Ruijia; Yang, Junjie; Jiang, Ping; Jin, Ling; Ma, Jing; Huang, Rong; Ma, Nan; Jiang, Fagang
Abstract : Aims: To explore the role of the suppressor of cytokine signalling 3 (SOCS3) gene in Graves' ophthalmopathy (GO) patients. Methods: A case–control study was conducted in a Chinese Han population by recruiting 114 Graves' disease (GD) patients with GO and 156 GD patients without GO. We determined SOCS3 mRNA and protein levels in Epstein–Barr virus-transformed lymphoblastoid cell lines (EBV-LCLs) from peripheral blood mononuclear cells (PBMCs) by quantitative real-time (QRT)-PCR analysis and western blot analysis. We also genotyped five single nucleotide polymorphisms (SNPs) in the SOCS3 locus (SOCS3 rs12952093, rs4969170, rs4969168, rs4969169 and rs2280148) in all 270 GD patients using ligase detection reaction and multiplex PCR analyses. QRT-PCR and western blot assays were then performed to compare SOCS3 mRNA and protein levels between the rs4969170 AA and GG genotype groups from 20 GO patients. Results: Basal SOCS3 mRNA and protein expression levels were significantly increased in patients with GO (p<0.05). The SOCS3 rs4969170 AA genotype was strongly associated with GO (OR=3.5, 95% CI 1.6 to 7.5, p=0.001). The AA genotype carriers had significantly higher SOCS3 mRNA and protein levels than those with the GG genotype (p<0.05). Conclusions: Patients with GD who carry the AA genotype of the rs4969170 SNP in SOCS3 are more susceptible to the development of GO.